2022
DOI: 10.15823/p.2022.146.6
|View full text |Cite
|
Sign up to set email alerts
|

Resilience factors in students with Disabilities at a Portuguese University

Abstract: This paper explores resilience factors identified in students with disabilities at a Portuguese public university. This research employs a mixed approach using qualitative and quantitative methods. For this, we used a retrospective, multiple case study design, and individual interviews were conducted with students with disabilities. We conclude that resilience, self-esteem, family support, subjective well-being and psychological well-being are protective factors that contribute to a good adaptation and better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Although no other sociodemographic variable has been found to contribute to influence resilience and affect, other studies have reported that self-esteem, family support, subjective well-being, psychological well-being [ 49 ], regular sleep, perceived stress, well-being [ 50 ], empathy, responsibility, optimism, hope and interpersonal skills (communication, self-efficacy, self-control, autonomy, problem-solving) [ 51 ] may influence resilience levels. On the other hand, perceived teaching quality and professors’ communication technology competence [ 52 ], self-regulatory capacity (boredom, awareness, goal, and emotion control) [ 53 ], self-efficacy [ 54 ], bedtime procrastination, and mobile phone addiction [ 55 ] may influence positive and negative emotions in students.…”
Section: Discussionmentioning
confidence: 99%
“…Although no other sociodemographic variable has been found to contribute to influence resilience and affect, other studies have reported that self-esteem, family support, subjective well-being, psychological well-being [ 49 ], regular sleep, perceived stress, well-being [ 50 ], empathy, responsibility, optimism, hope and interpersonal skills (communication, self-efficacy, self-control, autonomy, problem-solving) [ 51 ] may influence resilience levels. On the other hand, perceived teaching quality and professors’ communication technology competence [ 52 ], self-regulatory capacity (boredom, awareness, goal, and emotion control) [ 53 ], self-efficacy [ 54 ], bedtime procrastination, and mobile phone addiction [ 55 ] may influence positive and negative emotions in students.…”
Section: Discussionmentioning
confidence: 99%